قبال کا تصور تعلیم و تربیت (اسلام کے تناظر میں ): Iqbal’s Concept of Education and Training (In the Perspective of Islam) - ڈاکٹر یاسمین کوثر (Tashkeel e Jadeed, 2024)
Allama Iqbal was a poet Philosopher and thinker. He expressed his views in poetry based on the Quran and Sunnah. He belonged to a religious family. His parents and teachers like Mir Hassan Played a fundamental role in his education and training. He was an orthodox Muslim and a lover of Rasool Akram (Peace be upon him). In his poetry the aspect of love for religion of Islam and love for the prophet is prominent. A Muslim’s Religion is not complete without believing in Prophet. In the Quran Allah has ordered the Muslims to obey his prophet as well as himself. Iqbal wanted the training of our new generation according to the principles of Islamic religion. He wished that our new generation must acquire the modern education of science and arts, but it should not have the aspect of atheism, rather the teaching of religion of Islam should be prominent and should be trained in self-realization, because success of the world and hereafter depends upon the following of Quran and Sunnah. Allama Iqbal wants to make the youth of the nation, Through the light of education, the winner of the battle of life and consider education as the most effective means for this purpose. According to Iqbal’s teaching when a Muslim loyal to Allah and his prophet, Almighty Allah puts the pen of destiny in his hand. This article consists of research analysis of Iqbal’s teaching regarding modern education.